تأثير المغذيات والحرارة في النمو والتركيب الكيميائي للطحلب الأخضر Chlorella vulgaris - حمود, نديم; ميهوب, حامد; علان, طارق (Latakia University Journal -Biological Sciences Series, 2016)
أُجريت في هذا البحث دراسة تأثير تراكيز مختلفة من النترات والفوسفات ومستخلص التربة في النمو والتركيب الكيميائي للطحلب الأخضر Chlorella vulgaris المعزول من بعض المسطحات المائية المحلية، عند ثلاث درجات حرارة (20 – 25 – 30 درجة مئوية)، بلغ أعلى معدل نمو 4.66 خلية/ساعة وأقل زمن تضاعف1.55 ساعة وذلك عند درجة حرارة 25 درجة مئوية وعند تركيز 1 غ/ل نترات و0.05 غ/ل فوسفات و10مل/100 محلول تربة، حيث وصل عدد الخلايا إلى 59423.61 خلية/مل في اليوم 22 من الاستزراع.اختلف التركيب الكيميائي للطحلب باختلاف درجة الحرارة وتركيب الوسط المغذي اذ بلغ أعلى محتوى بروتيني 48.36 %عند التركيز الأعلى من المغذيات وعند درجة حرارة 25 درجة مئوية، وأعلى تركيز للدسم 19.78% عند درجة حرارة 25 درجة مئوية وتركيز 0.1 غ/ل نترات و0.01 غ/ل فوسفات و6مل/100 محلول تربة، أما تركيز السكريات فكان الأقل حيث كانت أعلى نسبة 17.41% عند درجة حرارة 20 درجة مئوية.The effect of different concentrations of nitrate and phosphate and soil extract on the total growth and chemical composition to the green algae Chorella vulgaris isolated from some localaquatic habitats had studied in this research, at three type of temperature (30 , 25, 20), the maximum total growth reached up to 4.66 Cell/h and the lowest duplicated time was 1.55 h at temperature 25ºC and at concentration of nitrate 1 g/L , 0.05 g/L of phosphate, and 10/100 mL of soil solution , while the number of cells reached to 59423,61 cell/mL at the day 22 of cultivation.The chemical composition differed by the changing of temperature and nutrient medium composition , while the maximum protein content reached to 48.36 % at the maximum concentration of nutrients and 25 ºC of temperature , the maximal concentration of lipid was 19,78 % at temperature 25ºC and concentration of nitrate 0.1 g/L and 0.01 of phosphate and 6/100 mL of soil solution , the concentration of carbohydrates were the lowest where the maximal ratio was 17.41 % at temperature 20ºC .